ANALISIS STRATEGI KONSERVASI TANAH DI LAHAN PERTANIAN DAERAH ALIRAN SUNGAI BRIBIN GUNUNGKIDUL - Siwi Pambayun, Lintang Panjali; Widyatama, Adiprasetya (Agriculture Faculty of Flores University, 2025)
Watershed is an area that has great potential for degradation. Degraded land is characterized by the loss of topsoil due to erosion. Understanding land sensitivity to erosion plays a crucial role in determining effective soil conservation methods to prevent land degradation, especially agricultural land. This study was conducted in the Bribin Watershed, Gunungkidul, with the aim of analyzing the level of land vulnerability to erosion on agricultural land. Data analysis was carried out spatially by utilizing land system maps and land cover maps. Recommendations for soil conservation on agricultural land are determined based on the level of land sensitivity that has been analyzed. Land sensitivity to erosion in the Bibrin Watershed is classified into four categories, namely very low (0.02%), low (5.03%), moderate (27.82%), and high (67.13%). Various watershed management strategies are applied by considering the level of land sensitivity. The creation of gulud terraces and the return of topsoil as well as reforestation on ex-mining land are soil conservation efforts in controlling erosion.